PENGEMBANGAN KECERDASAN MAJEMUK (MULTIPLE NTELLIGENCES) DI MADRASAH - Aryani, Wiwik Dyah; Rahmat, Asep; Darmawan, M.Darmawan; Abduh, Muhamad; Rikza, M.Rikza (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2022)
Intelligence is not black and white; there are several aspects of human intelligence, not just one. At least, there are nine types of human intelligence called multiple intelligences. Nine types of intelligence greatly affect a person's success in the competition of life. This paper will discuss the strategy of developing multiple intelligences in madrasah as one of the Islamic educational institutions. In fact, the practice of education in madrasah shows that the principle of multiple intelligences has long swallowed some of the ingredients that are integrated with each other. The development of potential learners in madrasah has long been developing in several aspects of emotional, intellectual, spiritual, social and individuality intelligence in accordance with Islamic teaching principles.ABSTRAKKecerdasan tidak hitam putih ada beberapa aspek kecerdasan manusia bukan hanya satu saja. Paling tidak, ada sembilan jenis kecerdasan manusia yang disebut multiple intelligences. Sembilan jenis kecerdasan sangat mempengaruhi keberhasilan seseorang dalam persaingan hidup. Makalah ini akan membahas strategi pengembangan kecerdasan majemuk di madrasah sebagai salah satu institusi pendidikan Islam. Kenyataannya praktik pendidikan di madrasah menunjukkan bahwa prinsip kecerdasan ganda telah lama menelan beberapa bahan yang saling terintegrasi satu sama lain. Perkembangan pelajar potensial di madrasah telah lama berkembang dalam beberapa aspek kecerdasan emosional, intelektual, spiritual, sosial dan individualitas sesuai dengan prinsip pengajaran Islam.